P-222 Timely support for carers of people at the end of life through the adult carer support plan. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Carduff, Emma; Swan, Susan; Meade, Richard
Abstract : Introduction: The Carers (Scotland) Act (2016) places a duty on local authorities to prepare an Adult Carer Support Plan (ACSP) and Young Carer Statement for any carer who requests one, or is identified as such. From 2019, this will be assisted by a fast track process for carers of people in their last six months of life. Timely identification of unpaid carers, assessment and support can; reduce the overwhelming pressure of caregiving, increase competence, confidence, satisfaction and the quality of the care given. Aim: To provide evidence on the supportive needs of carers to inform recommendations regarding the timescale for the creation of fast tracked ACSPs under the Carers (Scotland) Act (2016). Methods: The study triangulated data from a literature review, qualitative secondary analysis (n=19 interviews; three focus groups) and two primary focus groups with bereaved carers (n=11). Results: Themes included; barriers to and triggers for identification and needs including physical support, psychological support, respite, information, communication, co-ordination and competing demands. Additional themes were speed of decline and end of life care. Conclusion: Health and social care professionals need to take a radical, reactive move to presume that every patient has a carer, and ensure they understand their entitlements. Carer identification is everyone's responsibility and it should be the ambition of the Carer (Scotland) Act (2016) that this happens early in the illness trajectory. In so doing, rapid assessment and support can be initiated to help carers navigate and cope with an uncertain, often rapidly deteriorating illness trajectory.